PROTOTIPE GAME EDUKASI BAHASA INGGRIS UNTUK SISWA SEKOLAH DASAR (SD) - Made Dona Wahyu Aristana; Dewa Ayu Putri Wulandari; I Dewa Putu Gede Wiyata Putra (LPPM Universitas Dhyana Pura, 2023)
ABSTRACTEnglish is an international language that is used almost all over the world. Bali as a national and international tourist destination really needs English as the language of instruction in the tourism industry, so the introduction of English needs to be done early. Currently English has been taught from Elementary School (SD) to Higher Education. The teaching method used so far is to explain directly in class. The teacher explains the material orally or by writing on the blackboard. This teaching method is considered too monotonous and less interesting so that students become bored. Using education games students can play while learning, making it more fun. Education games are not only entertaining, but also educational. Therefore, it is very suitable to be applied to elementary school students. The method used is the prototype method which consists of four stages, namely, Communication, Quick Plan and Modeling Quick Design, Construction of prototype, and Development Delivery & Feedback. From the evaluation, it was found that the prototype of this English educational game was